Prevalence and Predictors of Contrast-Induced Nephropathy (CIN) in Patients with ST-Segment Elevation Myocardial Infarction (STEMI) Undergoing Percutaneous Coronary Intervention (PCI): A Meta-Analysis - Huan He; Xiao-Rui Chen; Yun-Qing Chen; Tie-Sheng Niu; Yi-Meng Liao (Journal of Interventional Cardiology)
Background. Contrast-induced nephropathy (CIN) becomes more and more frequent after percutaneous coronary intervention (PCI) in patients with ST-segment elevation myocardial infarction (STEMI). There have been no reported meta-analyses to determine the role of these risk factors in predicting CIN in patients with STEMI undergoing PCI. So we made this meta-analysis to summarize the incidence of CIN in patients with STEMI undergoing PCI and to study associations between CIN and several risk factors that are mentioned in most prevention guidelines. Hypothesis. The overall incidence of CIN in patients with STEMI undergoing PCI is not low. Many risk factors could influence the occurrence of CIN, such as hypertension, diabetes mellitus (DM), and lower estimated glomerular filtration rate. Methods. Databases, including PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), and Chinese BioMedical (CBM), were searched for articles published before May 21, 2019, to identify all relevant studies on CIN. The pooled data were analyzed using either fixed-effects or random-effects models depending on heterogeneity (assessed via the I2 index). Results. Twelve articles encompassing a total of 6342 patients were included. The overall pooled CIN incidence was 13.3% (95% CI: 10.4–17.1). The forest plots showed positive associations between CIN and the presence of hypertension, diabetes mellitus, history of prior myocardial infarction, age, damaged left anterior descending artery, Killip class ≥2, decreased left ventricular ejection fraction, lower estimated glomerular filtration rate, and left ventricular ejection fraction <40%; the odds ratios for these factors were 1.85 (95% CI: 1.57–2.18; p<0.00001), 1.83 (95% CI: 1.47–2.29; p<0.00001), 2.14 (95% CI: 1.46–3.14; p<0.0001), 7.79 (95% CI: 5.24–10.34; p<0.00001), 1.92 (95% CI: 1.15–3.22; p=0.01), 3.12 (95% CI: 2.21–4.40; p<0.00001), −6.15 (95% CI: −9.52 to −2.79; p=0.0003), −15.06 (95% CI: −24.75 to −5.36; p=0.002), and 5.53 (95% CI: 1.10–27.95; p=0.04), respectively. Conclusion. The overall incidence of CIN in patients with STEMI undergoing PCI was not low and was closely associated with hypertension, diabetes mellitus, history of prior myocardial infarction, age, damaged left anterior descending artery, Killip class ≥2, decreased left ventricular ejection fraction, lower estimated glomerular filtration rate, and left ventricular ejection fraction <40%.